FIGURATIVE LANGUAGE IN POE’S BRIDAL BALLAD - Fatnia Paramitha Makatita (Bajang Institute, 2022)
Figurative language is an essential element in literary works especially in poetry. It helps authors in emphasize meaning of their works and also drawn the reader in the beauty the language. Edgar Allan Poe was one of author that used various types of figurative languages in his works. The aim of this research is to elaborate figurative languages in one of Poe’s poetry Bridal Ballad. The data were collected from text and analyzed by employing descriptive-qualitative analysis. The result of this research that there are five types of figurative languages: alliteration, anaphora, irony, metaphor, and simile